Immunotherapy for osteosarcoma: Where do we go from here?. Issue 9 (19th June 2018) - Wedekind, Mary F.; Wagner, Lars M.; Cripe, Timothy P.
Abstract: Osteosarcoma is the most common bone tumor in children and young adults, with few advances in survival and treatment, especially for metastatic disease, in the last 30 years. Recently, immunotherapy has begun to show promise in various adult cancers, but the utility of this approach for osteosarcoma remains relatively unexplored. In this review, we outline the mechanisms and status of immunotherapies currently in clinical trials as well as future therapies on the horizon, and discuss their potential application for osteosarcoma.